(untitled) (Stavební obzor - Civil Engineering Journal, 2023)
The design parameters are one of the important factors to ensure the quality of asphalt pavement design. In “Highway Asphalt Pavement Design Specification” (JTGD50-2017), the stander of China, used the asphalt mixture anti-pressure resilience modulus at a single temperature of 20 ℃ as the design metrics. However, asphalt mixture, as a sticky-bullet plastic material, shows different mechanical properties at different temperatures. China is a vast territory, and there are great differences between the high and low temperature value (m and n) of each region. Therefore, it is unreasonable to design asphalt pavement only with the asphalt mixture anti-pressure resilience modulus value at 20 ℃. Studies show that the design parameters using PG technology can improve the high temperature anti-rutting and low temperature cracking performance of asphalt pavement.